Thermoregulatory Responses and Morphometric Characteristics of Cane Rats (Thryonomys swinderianus) Fed Graded Levels of Elephant Grass and Concentrate Diets - Olorungbohunmi, T. O.; Oluwole, O. O.; Oludolapo, A. B.; Owosibo, A. O.; Ajayi, O. T.; Ajayi, S. R.; Olatundun, B. E.; Adedotun, A. O.; Olalere, M. O.; Oladele-Bukola, M. O.; et al. (European Journal of Applied Sciences, 2026)
The experiment was carried out at the cane rat unit of the Institute of Agricultural Research and Training, Ibadan, to evaluate the thermoregulatory responses and morphometric measurement of cane rats fed graded level of elephant grass and concentrate diet. The experiment was designed to determine the optimal grass- to -concentrate ratio that supports growth and thermal adaptability in captive cane rats. A total of thirty weaned cane rat between the ages of 5-6 months, procured from a reputable farmer with weight ranging from 1342g to 1350g were used for the experiment. The cane rats were allotted into 5 dietary treatments in a completely randomized design. Each treatment was replicated two times with three animals per replicate. The allotted animals were given elephant grass and formulated feeds in ratio: Treatment1 (T1) (25:75 % of mixture of elephant grass and concentrate), Treatment 2 (T2) (50:50 % of mixture of elephant grass and concentrate), Treatment 3 (T3) (75:25 % of mixture of elephant grass and concentrate), and Treatment 4 (T4) (100 % of concentrate) while Treatment 5 (T5) (100 % of elephant grass). The parameters measured were feed intake, weight gain and feed conversion ratio, which was calculated. Thermoregulatory parameters taken weekly were the rectal and head temperature. Also, the morphometric parameters which include body, tail and head length, heart-girth, and rump were also recorded. Data obtained were subjected to descriptive statistics and correlation analysis. It was observed that body weight gain and feed conversion ratio revealed significant (P>0.05) differences among the treatment means. The results indicated that cane rats on T1 with 75% concentrate had the highest feed conversion ratio while, highest feed intake and body weight gain was recorded in T4 (100% concentrate) followed by T3 (25% concentrate). The inclusion of 25% and 100% concentrate diets influenced morphological traits. It is, however, recommended that the optimum growth performance of cane rats was achieved at T3 (25% concentrate to 75%) elephant grass diet considering the growth response and feed conversion ratio obtained from the present study.